2013
DOI: 10.1080/00380768.2013.763382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different foliar zinc application at different growth stages on seed zinc concentration and its impact on seedling vigor in rice

Abstract: This study evaluated how zinc (Zn) concentration of rice (Oryza sativa L.) seed may be increased and subsequent seedling growth improved by foliar Zn application. Eight foliar Zn treatments of 0.5% zinc sulfate (ZnSO 4 Á 7H 2 O) were applied to the rice plant at different growth stages. The resulting seeds were germinated to evaluate effects of seed Zn on seedling growth. Foliar Zn increased paddy Zn concentration only when applied after flowering, with larger increases when applications were repeated. The lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 44 publications
5
72
1
9
Order By: Relevance
“…Application of ZnSO4 compared to Zn-EDTA releases more Zn at early stages. Zn-EDTA is a slow release nutrient fertilizer and it becomes more available from the vegetative growth up to the maturity (Boonchuay et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Application of ZnSO4 compared to Zn-EDTA releases more Zn at early stages. Zn-EDTA is a slow release nutrient fertilizer and it becomes more available from the vegetative growth up to the maturity (Boonchuay et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…E et al (2005) found that an increase in the amount of P fertilizer applied enhanced the Mg concentration in milled rice and that a rational application of K increased the accumulation of Fe, Zn, Cu and Mn in milled rice. Boonchuay et al (2013) confirmed that the Zn concentration of rice grains could be effectively increased by foliar application of ZnSO 4…”
Section: Introductionmentioning
confidence: 50%
“…Insufficient intake of these mineral elements from food results in the impairment of human health, such as the occurrence of anemia (Shan, 2006). It has been reported that approximately one-third of the world's population suffers from Fe and Zn malnutrition, a problem that is particularly severe in developing countries (Boonchuay et al, 2013). As a staple cereal crop, rice (Oryza sativa L.) provides not only carbohydrates but also protein, vitamin and mineral nutrition for more than half of the world's population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation between seed quality parameters and seedZn content: There is evidence in literature demonstrating the role and association of Zn in enhancing the seed germination and vigour (Rengel 2008 andBoonchuay et al, 2013). Zinc is involved in biosynthesis of plant hormone, indole acetic acid (IAA), auxin metabolism and is component of variety of enzymes like, carbonic anhydrase, alcohol dehydrogenase, glutamic dehydrogenase etc.…”
Section: Resultsmentioning
confidence: 99%